Прибор для элементного анализа состава материалов с помощью спектра масс - Косуля, Л.В.; Вербицкий, В.Г. (Технология и конструирование в электронной аппаратуре, 2016)
Разработана структура и основные функциональные узлы прибора-анализатора многоэлементных веществ в масштабе реального времени, который позволяет за короткое время и с высокой точностью проводить анализ материалов. Розроблено структуру і основні функціональні вузли приладу-аналізатора багатоелементних речовин в масштабі реального часу, який дозволяє за короткий час і з високою точністю проводити аналіз матеріалів. The article reveals the development of the structure and basic functional units of the real time analyzer for multi-element substances, which allows short time and high accuracy material analysis. The article reveals the design and sequence of operations for the assembly of an experimental device sample. Technical requirements for the LSI control device have been defined and used as the basis for the development of circuit diagram. Functionally the device consists of three modules: measurement module, switching module and test pulses driver. The measurement module implements the communication between PC and LSI and directs the work of other nodes. The switching module consists of miniature electromechanical relays that allow implementing various combinations for connection of LSI terminals to the measuring channels of transducers. Shaper of test pulses provides the ability to adjust necessary parameters of the pulse: amplitude U1 and U2, period, delay between U1 and U2, generation of a specified number of pulses on the test LSI terminals.